ANALISIS KELIMPAHAN DINOFLAGELLATA EPIBENTIK PADA Sargassum sp DI PERAIRAN TELUK BUNGUS PROVINSI SUMATERA BARAT - Putri Wahyuni; Thamrin Thamrin; Sofyan Husein Siregar (Program Pascasarjana Universitas Riau, 2016)
Epibentik Dinoflagellates can be epiphytic (associated with seagrasses or macroalgae). This study used a survey method with Sargassum sp as a Dinoflagellata attachment. Research on the abundance of Dinoflagellata was conducted in Bungus Buy in November 2014. Based on samples collected, nine Dinoflagellates were found, where five of them were potentially toxic. They were Chatonella, Gonyaulax, Ceratium, Dinophysis, Prorocentrum, Gambierdiscus, Ceratium, Alexandrium, Pyrodinium and Scrippsiella with an abundance of 5231-12177 cell/g. The results showed no relationship between the concentration of nitrate and phosphate on the abundance Dinoflagellates. The nitrate concentrations ranging from 0.0175 to 0.0312 mg / l and phosphate concentrations ranging from 0.0181 to 0.0354 mg / l.